The role of TIGAR in nervous system diseases - Huang, Bei; Lang, Xiaoling; Li, Xihong (Frontiers in Aging Neuroscience, 2022)
TP53-induced glycolysis and apoptosis regulator (TIGAR) mainly regulates pentose phosphate pathway by inhibiting glycolysis, so as to synthesize ribose required by DNA, promote DNA damage repair and cell proliferation, maintain cell homeostasis and avoid body injury. Its physiological functions include anti-oxidative stress, reducing inflammation, maintaining mitochondrial function, inhibiting apoptosis, reducing autophagy etc. This paper reviews the research of TIGAR in neurological diseases, including stroke, Parkinson’s disease (PD), Alzheimer’s disease (AD), seizures and brain tumors, aiming to provide reference for the development of new therapeutic targets.